Pengukuran Lahan Pertanian Untuk Meningkatkan Efisiensi Produksi - Arkhipus Gulo (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Agriculture is one of the most important sectors in the Indonesian economy. However, agricultural production in Indonesia still faces various challenges, such as low productivity and lack of efficiency. One way to increase the efficiency of agricultural production is to carry out accurate measurements of agricultural land. This research aims to develop an accurate and efficient method for measuring agricultural land. The research results show that the developed agricultural land measurement method can increase agricultural production efficiency by 25%. Therefore, this research can be a reference for farmers and the government in increasing the efficiency of agricultural production.